Mechanistic Understanding of Candida albicans Biofilm Formation and Approaches for Its Inhibition - Atriwal, Tanu; Azeem, Kashish; Husain, Fohad Mabood; Hussain, Afzal; Khan, Muhammed Nadeem; Alajmi, Mohamed F.; Abid, Mohammad (Frontiers in Microbiology, 2021)
In recent years, the demand for novel antifungal therapies has increased several- folds due to its potential to treat severe biofilm-associated infections. Biofilms are made by the sessile microorganisms attached to the abiotic or biotic surfaces, enclosed in a matrix of exopolymeric substances. This results in new phenotypic characteristics and intrinsic resistance from both host immune response and antimicrobial drugs. Candida albicans biofilm is a complex association of hyphal cells that are associated with both abiotic and animal tissues. It is an invasive fungal infection and acts as an important virulent factor. The challenges linked with biofilm-associated diseases have urged scientists to uncover the factors responsible for the formation and maturation of biofilm. Several strategies have been developed that could be adopted to eradicate biofilm-associated infections. This article presents an overview of the role of C. albicans biofilm in its pathogenicity, challenges it poses and threats associated with its formation. Further, it discusses strategies that are currently available or under development targeting prostaglandins, quorum-sensing, changing surface properties of biomedical devices, natural scaffolds, and small molecule-based chemical approaches to combat the threat of C. albicans biofilm. This review also highlights the recent developments in finding ways to increase the penetration of drugs into the extracellular matrix of biofilm using different nanomaterials against C. albicans.